Development of creativity and critical thinking skills: Findings from students participating in a PBL experience - Fernandes, Sandra (2023)
Finding ways to promote the development of skills needed for a successful transition of students from higher education to the labour market is an important issue that needs to be considered by teachers, when organizing the teaching and learning process. Active learning methods, in particular, Project Based Learning (PBL) have proven to be an effective teaching learning approach, bringing the reality of work to the classroom and thus improving the development of student skills. Creativity and critical thinking have been pointed out, in different studies, as one of the most relevant and necessary skills in the labour market since they support the development of societies. In addition, the increasing digitization of human work and the advancement of artificial intelligence reinforce the importance of developing these skills in students, since they are skills that are more difficult to automate and become one of the most valued by the job market. This paper aims to analyse how creativity and critical thinking are developed in the context of a PBL experience. The paper begins with an understanding of what is meant by creativity and critical thinking and then discusses the development of this competence through PBL. It ends with the analysis of a survey applied to students of the 3rd year of the Management degree, within the scope of the curricular unit called Information Systems for Management, which aimed to i) analyse how the teacher, throughout the project (PBL), contributes to the development of these competences and ii) to assess whether the students felt that PBL contributes to the development of these competences.